Thyroid transcription factor‐1 (TTF‐1) immunoreactivity is an adverse prognostic factor in endometrioid adenocarcinoma of the uterine corpus. Issue 6 (21st January 2014) - Ervine, Aaron; Leung, Sam; Gilks, C Blake; McCluggage, W Glenn
<x xml:space="preserve">Abstract</x> Aims It is known that thyroid transcription factor‐1 (TTF‐1) is expressed in a small percentage of primary gynaecological adenocarcinomas. Following the observation of TTF‐1 positivity in a number of endometrioid adenocarcinomas of the uterine corpus which behaved aggressively, we undertook immunohistochemical staining of a large series of endometrial adenocarcinomas of various types to investigate whether its expression is of prognostic significance. Methods and results TTF‐1 was performed on tissue microarrays containing 102 low‐grade (grades 1 or 2) endometrioid adenocarcinomas, 101 grade 3 endometrioid adenocarcinomas, 89 serous adenocarcinomas and 29 clear cell carcinomas. All categories of endometrial adenocarcinoma exhibited TTF‐1 staining in a small subset of cases (2% low‐grade endometrioid, 11% grade 3 endometrioid, 9% serous, 7% clear cell). TTF‐1 was less frequently expressed in low‐grade endometrioid adenocarcinomas compared to other subtypes. Endometrioid adenocarcinomas which expressed TTF‐1 had a statistically significant worse prognosis with poorer disease‐specific survival, and this was also statistically significant in the group of low‐grade endometrioid adenocarcinomas. Conclusions Our study confirms that TTF‐1 is expressed in a small, but not insignificant, proportion of endometrial adenocarcinomas. TTF‐1 positivity in low‐grade endometrioid adenocarcinomas is an indicator of poorer prognosis.